In vitro assessment of seminal traits and fertility parameters in fresh semen of Sahiwal bulls - RAMCHANDRAN, N; VERMA, G S; GUPTA, A K; RAINA, V S; MOHANTY, T K; SINGH, M K (The Indian Journal of Animal Reproduction, 2023)
Eight Sahiwal bulls maintained at Artificial Breeding Complex, National Dairy Research Institute, Kamal, Haryanawere u~ed to evaluate the seminal attributes and fertility parameters from fresh semen samples. The overall least squares meansf~r various seminal traits and fertility parameters were reported. The effect of bull was significant (P
Keywords: Semen evaluation; in vitro fertility tests; CASA; Sahiwal bull